Indonesia’s First Makanan Bergizi Gratis Starting in 2025-2026: Case Studies in Class of Supply Chain Management - Samuel PD Anantadjaya; Irma M Nawangwulan; Alimanto Chu (Journal of Sustainable Community Development (JSCD), 2026)
Indonesia’s Makan Bergizi Gratis (MBG) program, or Free Nutritius Meals (FNM), which was introduced by President Prabowo Subianto in 2025, basically sits as a huge public welfare effort meant to give free nutritious meals to about 82–83 million people, mostly school age children, pregnant women, and breastfeeding mothers. The program is not only about tackling malnutrition and child stunting, it is a strategic national policy tool meant to push economic growth, modernize the food supply chain, and form stronger human capital. In this paper, a qualitative case study approach is used so MBG is looked at like an operational, plus public sector management problem, by reviewing policy documents, program records, and what international school feeding practices usually look like. The results show that even though the program has huge potential to improve national nutrition and to strengthen local economies, its implementation still gets slowed down by systemic risks. Those risks include food safety weak points, budget inefficiencies, governance breakdowns, and distribution obstacles across Indonesia’s archipelago, which is not a small thing at all. The study then concludes that for MBG to stay viable in the long run, it needs to move away from fully universal coverage toward a semi-targeted fiscal allocation model, plus it has to create strict multi-layer governance and run integrated digital monitoring. MBG is really a complicated national systems matter, so it needs centralized standards while local areas carry out execution in a more decentralized way in order to push inclusive development that actually reaches everyone.